Social-scientific criticism: Perspective, process and payoff. Evil eye accusation at Galatia as illustration of the method - Elliott, John Hall (HTS teologiese studies, 2011)
This article explores a presentation of the method, emergence and contribution of social-scientific criticism (SSC) as an inter-disciplinary operation of New Testament exegesis. A description of ancient evil eye belief and practice and its appearance in Paul’s letter to the Galatians illustrates how the method contributes to a more accurate translation of the biblical text, a clarification of its logic and a fuller understanding of the social dynamics involving Paul and his opponents.